Political Party Coup: Anomalies within the Democratic Party - Dewi Analis Indriyani; Zaihan Harmaen Anggayudha (Jurnal Penelitian Hukum De Jure, 2021)
The Democratic Party dispute raises the view that there is dualism within the Democratic Party. The issue of the Democratic Party Leadership Takeover Movement (GPKPD) led to the dismissal of several of its cadres. The dispute escalated with the holding of the Extraordinary Congress (KLB) in Deli Serdang on March 5, 2021. One of the things which triggered the holding of the KLB by the opposition was the management of Agus Harimurti Yudhoyono (AHY). Apart from being seen as not agreeing with Article 83 paragraph (2) letter b in the 2020 Democratic Party's Articles of Association and Bylaws, the validity of the AHY management along with the preparation of the Articles of Association and Bylaws in 2020 was also questioned by several cadres. In addition, the political dynasty by the Cikeas family was also highlighted. This Democrat Party dispute becomes more interesting to study because the AHY opposition's KLB involves an external party who is a state official. This article is socio-legal study that was carried out textually and critically to laws and regulations and policies. The undemocratic management and election of the general chairman in providing opportunities for other cadres to compete in a transparent and fair manner created internal turmoil that led to the dismissal of several cadres. There are anomalies within the Democratic Party with the increasingly clear Democratic Party as a dynastic party, undemocratic KLB arrangements, to the implementation of KLB which is a structural conflict of the Democratic Party with non-structural collectives.